True Cost of Happiness : The Real Story Behind Managing Your Money - Tisdale, Stacey, 1966- and Kennedy, Paula Boyer, 1956- (Hoboken John Wiley & Sons, 2007)
Get personal money management advice that make sense. In The True Cost of Happiness, financial journalist Stacey Tisdale and financial expert Paula Boyer Kennedy offer unique Life Planning techniques that allow you to successfully plan your financial future and take complete control of your finances.
Include Index
Keywords: Awareness -- Finance, Personal--Psychological aspects -- Self-actualization (Psychology)